2016
DOI: 10.1155/2016/8175768
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Serum 25-Hydroxyvitamin D Concentrations among a Sample of Egyptian Schoolchildren

Abstract: Objective. To assess the level of 25-hydroxyvitamin D status among a sample of Egyptian schoolchildren and to evaluate predictors of deficiency and insufficiency. Subjects and Methods. A cross-sectional study comprising 200 prepubescent schoolchildren aged from 9 to 11 years was performed. A questionnaire including frequency of midday sun exposure, milk intake, physical activity, and level of maternal education was taken. Body mass index (BMI) was calculated; serum 25-hydroxyvitamin D [25(OH)D], serum calcium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
(47 reference statements)
0
15
1
1
Order By: Relevance
“…That is because while they still benefit from breast milk, nursing toddlers may not consume as much of foods such as cow’s milk and other dietary sources of the vitamin as needed [ 31 ]. A cited study which addressed the predictors of serum 25-hydroxyvitamin D concentrations among a sample of Egyptian schoolchildren reported similar results; the authors stated that the difference in gender may be due to lifestyle factors such as spending more time indoors, less time outdoors, and coverage of skin by clothing that could affect cutaneous synthesis of vitamin D [ 32 ]. However, this cannot be applied to our population due to the younger age of girls in the current study, as none of them wear a hijab.…”
Section: Discussionmentioning
confidence: 94%
“…That is because while they still benefit from breast milk, nursing toddlers may not consume as much of foods such as cow’s milk and other dietary sources of the vitamin as needed [ 31 ]. A cited study which addressed the predictors of serum 25-hydroxyvitamin D concentrations among a sample of Egyptian schoolchildren reported similar results; the authors stated that the difference in gender may be due to lifestyle factors such as spending more time indoors, less time outdoors, and coverage of skin by clothing that could affect cutaneous synthesis of vitamin D [ 32 ]. However, this cannot be applied to our population due to the younger age of girls in the current study, as none of them wear a hijab.…”
Section: Discussionmentioning
confidence: 94%
“…In Egypt, a cross-sectional study by Abu Shady et al of 200 school children, aged 9–11 years, reported vitamin D inadequacy (serum 25(OH)D 50–74.8 nmol/L) and insufficiency (serum 25(OH)D < 50 nmol/L) in 15% and 11.5% of the cohort, respectively [19]. Obesity, low physical activity, limited sun exposure, and a mother with low educational level were significant predictors of inadequacy.…”
Section: Prevalence Of Micronutrient Deficiencies In the Middle Eastmentioning
confidence: 99%
“…Prevalence of vitamin D deficiency and insufficiency (serum 25(OH)D < 50 nmol/L) in the Middle East by age and gender (Sources: KSA [11,24,40,48]; UAE [20,30]; Lebanon [18,34]; Egypt [19,26,27,44]).…”
Section: Figurementioning
confidence: 99%
“…There are potential confounding factors affecting vitamin D status, which are also known to play a role in increased risk of metabolic syndrome in children. For example, increased use of TV, video or computers [ 37 , 38 , 39 ], less physical activity [ 33 , 38 , 39 , 40 , 41 , 42 , 43 ], low sun exposure [ 33 , 41 , 42 , 43 , 44 ], low levels of milk consumption [ 33 , 37 , 43 , 45 ] and high levels of soft drink consumption [ 45 ] can increase the risk of developing vitamin D deficiency in children aged 1–18 years. At age 6–16 years, children were vitamin D deficient in spring and winter [ 35 , 36 , 39 , 41 , 46 , 47 , 48 ] and girls were found to be more vitamin D deficient than boys [ 33 , 34 , 36 , 37 , 48 , 49 , 50 ].…”
Section: Vitamin D In Children: Assessment Of Status and Deficiencmentioning
confidence: 99%